Development of a Functional Nanobody Targeting Programmed Cell Death Protein-1 as Immune Checkpoint Inhibitor - Hosseininejad-Chafi, Mohammad; Kianmehr, Zahra; Pooshang-Bagheri, Kamran; Kazemi-Lomedasht, Fatemeh; Behdani, Mahdi (Current pharmaceutical design, 2023)
Programmed cell death protein 1 (PD-1) is a membrane receptor that is expressed on the surface of various immune cells, such as T cells, B cells, monocytes, natural killer T cells, and dendritic cells. In cancer, the interaction between PD-1 and its ligand PD-L1 suppresses the activation and function of T lymphocytes, leading to the impairment and apoptosis of tumor-specific T cells. This mechanism allows cancer cells to evade the immune response and promotes tumor progression. Recombinant PD-1 protein was produced and used to immunize a camel. A nanobody library was generated from the camel's peripheral blood lymphocytes and screened for PD-1 binding. A specific nanobody (3PD9) was selected and characterized by affinity measurement, western blotting, and flow cytometry analysis. The ability of the selected nanobody to block the inhibitory signal of PD-1 in peripheral blood mononuclear cells (PBMCs) was evaluated by measuring the level of interleukin-2 (IL-2). The selected nanobody showed high specificity and affinity for human PD-1. Western blot and flow cytometry analysis confirmed that 3PD9 could recognize and bind to human PD-1 on the cell surface. It was demonstrated that the level of IL-2 was significantly increased in PBMCs treated with 3PD9 compared to the control group, indicating that the nanobody could enhance the T cell response by disrupting the PD-1/PD-L1 interaction. The results suggested that the anti-PD-1 nanobody could be a promising candidate for cancer immunotherapy.